2015
DOI: 10.1021/acs.iecr.5b01422
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Formalin with Acetic Acid over Vanadium–Phosphorus Oxide Bifunctional Catalyst

Abstract: 11A new route to synthesizing acrylic acid from acetic acid and formalin by 12 one-step aldol condensation reaction was proposed and developed. V-P/ SiO 2 oxide 13 bifunctional catalysts were designed and prepared by ultrasonic impregnation method.14 The catalysts were characterized by XRD, BET, TEM, TG/DTA, and XPS, as well as 15 NH 3 , CO 2 -TPD, and pyridine-FTIR methods. Catalytic performance was evaluated 16 using a fixed-bed tubular microreactor operating with a CH 3 COOH/HCHO (HAc/FA) 17 molar ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 28 publications
5
40
0
Order By: Relevance
“…For example, Zhang et al 18 used P-doped Cs oxide supported on γ-Al 2 O 3 as catalysts and observed a high activity for the aldol condensation of Ma and FA, which was ascribed to the high density of weak acidic and weak basic sites on this material. Yang et al 19,20 investigated the performance of V and P oxides supported on SiO 2 and found that the textural, acid−base property and the ratio of V 4+ to V 5+ were important in determining the activity of the catalysts. Using SiO 2 , SBA-15, and HZSM-5 as supports for V−P oxides, Hu et al 21 found that the support type and the P/ V atomic ratio affect the acid−base property and the activity of these catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang et al 18 used P-doped Cs oxide supported on γ-Al 2 O 3 as catalysts and observed a high activity for the aldol condensation of Ma and FA, which was ascribed to the high density of weak acidic and weak basic sites on this material. Yang et al 19,20 investigated the performance of V and P oxides supported on SiO 2 and found that the textural, acid−base property and the ratio of V 4+ to V 5+ were important in determining the activity of the catalysts. Using SiO 2 , SBA-15, and HZSM-5 as supports for V−P oxides, Hu et al 21 found that the support type and the P/ V atomic ratio affect the acid−base property and the activity of these catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridine‐FTIR was used to characterize the acid types of the catalysts, and the corresponding spectra of pyridine desorbed at 200 °C on both the modified and unmodified catalysts are shown in Figure . It was obvious that all the catalysts had a strong adsorption peak around 1450 cm −1 which indicated the pyridine adsorption on Lewis acid sites . A relative weak band around 1490 cm −1 which indicated the adsorption on either Lewis or Brønsted acid sites, also appeared in all the spectra.…”
Section: Resultsmentioning
confidence: 90%
“…Various catalysts have been employed in the aldol condensation reaction of acetic acid and formaldehyde, such as acids, bases and base–acid bifunctional catalysts, among which acid–base bifunctional catalysts attract most attention owing to the cooperation between acid and base active sites. The acidic sites, especially the weak ones, are essential to trigger the aldol condensation reaction, and the high acid amount is favorable for formaldehyde conversion.…”
Section: Resultsmentioning
confidence: 99%
“…reported a V‐P‐O catalyst comprising mainly (VO) 2 P 2 O 7 and δ ‐VOPO 4 , effective for converting acetic acid with formaldehyde to acrylic acid. Yang et al . found that weak acid sites, base sites and the ratio of V 4+ to V 5+ were essential for aldol condensation reactions.…”
Section: Introductionmentioning
confidence: 99%